Individual differences and stability of dynamics among self-concept clarity, impatience, and negative affect. Issue 3 (2nd April 2020) - Ellison, William D.; Gillespie, Megan E.; Trahan, Alec C.
ABSTRACT: Self-concept clarity (SCC) is associated with behavioral and emotion regulation, although the nature of this link is unclear. SCC may serve as a self-regulatory resource or it may be a product of well-regulated behaviors and emotions. In two studies using experience sampling among undergraduates ( n = 46 and n = 36), we investigate whether models representing relationships among SCC, impatience, and negative affect (NA) states conform to these theories, are similar across individuals, and are stable across a one-month period. Results reveal substantial variation between persons in these dynamic relationships, suggesting that multiple SCC-relevant regulatory processes exist. These patterns were not stable from one month to the next, but changes in them related to changes in stress, suggesting higher-order regulation of these dynamics.